RETINAL IMPAIRMENT ASSOCIATED WITH LONG-TERM USE OF RITONAVIR AMONG HIV PATIENTS: A SYSTEMATIC REVIEW FOR PRIMARY EYE CARE PRACTICE - Zakirunallah - Karunia; Ivana Beatrice Alberta; Salsha Alyfa Rahmani (Indonesian Vitreoretinal Society, 2022)
Introduction: Ritonavir as part of Highly Active Antiretroviral Therapy (HAART) is a potent inhibitor of HIV protease that have been reported causing retinal impairment in the long term use. Primary eye care (PEC) is an integral part of primary health care that provides an early screening for drug induced retinal toxicity, by using a funduscopy examination. This study proposed to review and analyze some case reports conducted on long-term use of ritonavir that affects retinal impairment among HIV patients, in primary eye care practice. Methods: PubMed and Google Scholar were used to perform a systematic review of retinal impairment associated with long-term use of ritonavir among HIV patients. Using PRISMA 2020 Guidelines, nine case reports and one case series were included in this review. Result: Funduscopy mainly showed bilateral Retinal Pigment Epithelium (RPE) atrophy with hypertrophy or mottling. Two cases found bilateral crystalline deposits with pigment disruption. One case showed rounded hypopigmented lesion. Bilateral subtle annular pattern of RPE was found in one case. Bilateral retinitis pigmentosa-like appearance found in one case while another found unilateral hyperemic lesion at the left fovea. Conclusion: Retinal impairment detected on funduscopy occurred in HIV patients on long-term use of ritonavir.